Hypothesis Testing of The Unsecured Interest Rate Parity: the Case of USD/PLN and EUR/PLN in 2006–2010 - Śliwiński, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The aim of this article is to verify the research hypothesis that assumes the existence of profitable carry trade operations based on USD or EUR loans in Poland in the years 2006–2010. Summarizing the results of an empirical test should be noted that investors operating on the Polish money and currency markets could reach up substantial profits from carry trade operations. The achieved results therefore indicate that the International Fisher Effect is not a good tool for forecasting exchange rates in the short term. The results of the empirical test indicate that the decisive role in investors decisions was played by the expectations for the evolution of exchange rates in the future. Due to the unstable USD/PLN and EUR/PLN exchange rates it can therefore be concluded that (the not secured against currency risk) carry trade operations largely accounted for currency speculation.